1980
DOI: 10.3382/ps.0592738
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bile Acids and Lipase on Absorption of Tallow in Young Chicks

Abstract: White leghorn chicks were fed diets with 4% tallow supplemented with one of the following bile acids at .04%: cholic acid, chenodeoxycholic acid, dehydrocholic acid, deoxycholic acid, or sodium taurocholate. Cholic acid improved the absorption of tallow but not significantly; chenodeoxycholic acid significantly improved tallow absorption during days 0 to 7 but decreased it during days 14 to 21. The bile acids, dehydrocholic acid, deoxycholic acid, and sodium taurocholate had no significant effect on absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…The chicks at 1 week of age were the most responsive to an improvement in retention of lipid by bile acid supplementation confirming the trend that the younger the chick the greater the response (Fedde et al, I960;Katongole and March, 1980;Polin et al, 1980). The age of the chicken at which maximum absorption of dietary fats occurs has not been clearly defined.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The chicks at 1 week of age were the most responsive to an improvement in retention of lipid by bile acid supplementation confirming the trend that the younger the chick the greater the response (Fedde et al, I960;Katongole and March, 1980;Polin et al, 1980). The age of the chicken at which maximum absorption of dietary fats occurs has not been clearly defined.…”
Section: Discussionmentioning
confidence: 54%
“…This study revealed that chicks of a heavy breed had their lowest retention values as early as their first week of age. Thus, heavy breeds appear to be similar to light breeds, which were already so characterized (Carew et al, 1972;Gomez and Polin, 1976;Polin<?£ al, 1980).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Soy-lecithin is a by-product from the processing of soybean oil that, apart from being a source of energy, also serves as an emulsifier and has the potential to facilitate fat absorption (Lechowski et al, 1999). Studies have shown that dietary supplementation of bile salts improves emulsion formation and fat digestibility in chickens (Kussaibati et al, 1982;Polin et al, 1980a).…”
Section: Introductionmentioning
confidence: 99%